A Comprehensive Study of Various Trust Based Routing Schemes in WSN - Sandhya Vats (International Journal of Advanced Science and Technology, 2018)
The accelerated development of networks for communication and data transfer has paved the way to the vast application of these networks in various fields like military commands, surveillances, habitat monitoring, mobile communication systems etc. With such evolution come the serious challenges that can pose threats to these networks. Considering the sensitivity of the data being transmitted in such networks, the security has become a vital concern. The networks like Wireless sensor networks are often vulnerable to attacks, both internal and external attacks. Various security mechanisms like asymmetric encryption schemes can protect the networks from external attacks but when the security breach is caused by authenticated nodes inside the network, the aforementioned techniques fail miserably. In such scenario, trust and reputation models come to the rescue. Trust and reputation management system has proven to be an innovative solution in order to maintain a minimum level of security between the interacting entities in a network. This paper provides a vivid and elaborate analysis of various trust and reputation models on different networks and aims to discuss their efficiency in overcoming the security threats in a network.